THE INFLUENCE OF EMPLOYEE DEVELOPMENT AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT PT LOBARA DUTA ANUGRAH SURABAYA - Purnama Nigat, Gregorius; Wahjunianto, Hamy (Sekolah tinggi ilmu ekonomi pemuda, 2025)
PT Lobara Duta Anugrah Surabaya plays a key role in implementing industrial revolution and transfor-mation strategies. As a pioneer in human resource services in Surabaya, the company provides recruit-ment, training, and HR consulting.This study aims to analyze and describe the influence of employee de-velopment and work motivation on employee performance at PT Lobara Duta Anugrah Surabaya. Specif-ically, it seeks to determine: (1) the simultaneous effect of employee development and motivation on per-formance, (2) the partial (individual) effect of each variable, and (3) which variable has the most domi-nant influence.The research uses multiple linear regression analysis to examine how employee develop-ment and work motivation affect employee performance, both simultaneously and partially. Data were processed using SPSS version 31.00, and hypothesis testing was conducted through statistical tests and classical assumption tests. The results show that both employee development and work motivation signifi-cantly affect employee performance, both jointly and individually. Among the two variables, employee development has the most dominant influence, with a partial contribution of 40.6% to performance im-provement